In vivo dosimetry in breast tumours: comparison between the calculated and measured dose - Roma, Ana (2022)
Introduction – In vivo dosimetry is useful in measuring the dose administered to patients during treatment, assessing significant differences between the prescribed dose and the dose to the target volume and the organs at risk. Purpose – To compare the measured dose with the calculated dose in patients with breast tumors with and without a physical wedge. Methods – Entrance dose measurements using p-type diodes were performed for tangential fields and relative field-in-field in all 38 patients. Results – Statistically significant differences in open tangential fields (ρ=0.000) were verified. Discussion – Studies report significant systematic deviations between planned and measured doses. Conclusion – With this study, we conclude that there is no influence in the doses due to the presence of the physical wedge.